2020
DOI: 10.30598/10.30598//ijcr.2020.8-sul
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kualitas Nata De Corn Dari Ekstrak Jagung Kuning Muda Dengan Variasi Lama Fermentasi

Abstract: In this research, nata de corn has been made from the young corn extract by Acetobacter xylinum. This research aims to make nata de corn with the variation of fermentation days and analyze the quality of nata de corn have been done. Fermentation days have been varied to look for the optimum conditions to obtain maximum quality. The variation of fermentation days was 11, 12, 13, and 14 days. Mass of young corn as substrate was 150 g/L solution. Then, Substrate was fermented using Acetobacter xylinum. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
0
0
1
Order By: Relevance
“…The 7-day fermentation time is the exponential phase. Microbes multiply in this phase to create ideal products (Ramayanti & Giasmara, 2017;Sulistiyana, 2020 The optimum concentration of whey that is appropriate for making coconut milk nata de skim is 49.07% with the optimization response to the yield of coconut milk nata de skim shown in Table 6. The ideal coconut milk nata de skim yield value is 29.71%.…”
Section: Discussionmentioning
confidence: 99%
“…The 7-day fermentation time is the exponential phase. Microbes multiply in this phase to create ideal products (Ramayanti & Giasmara, 2017;Sulistiyana, 2020 The optimum concentration of whey that is appropriate for making coconut milk nata de skim is 49.07% with the optimization response to the yield of coconut milk nata de skim shown in Table 6. The ideal coconut milk nata de skim yield value is 29.71%.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil pengujian kadar serat berkisar 1% sampai 3%. Semakin besar kadar air pada BC maka kadar serat semakin kecil.Hasil ini sesuai dengan SNI 01-4317-1996, bahwa syarat mutu kandungan serat pada makanan maksimal 4.5% (Sulistyana, 2020). Kadar serat terbesar mencapai 3% ditunjukkan pada substrat leri, air tomat, dan kombinasi leritomat.…”
Section: Kadar Air Dan Seratunclassified
“…Sulistiyana [14] also found that light yellow corn extract can be used as an ingredient for making nata de corn with the optimum condition for 14 days of fermentation. The characterization of nata de corn from light yellow corn substrate includes the yield of 46.82%, the water content of 93.13%, and fiber content of 1.31%.…”
Section: Introductionmentioning
confidence: 98%